Acute Pharmacologic Degradation of a Stable Antigen Enhances Its Direct Presentation on MHC Class I Molecules - Moser, Sarah C.; Voerman, Jane S. A.; Buckley, Dennis L.; Winter, Georg E.; Schliehe, Christopher (Frontiers in Immunology, 2018)
Bifunctional degraders, also referred to as proteolysis-targeting chimeras (PROTACs), are a recently developed class of small molecules. They were designed to specifically target endogenous proteins for ubiquitin/proteasome-dependent degradation and to thereby interfere with pathological mechanisms of diseases, including cancer. In this study, we hypothesized that this process of acute pharmacologic protein degradation might increase the direct MHC class I presentation of degraded targets. By studying this question, we contribute to an ongoing discussion about the origin of peptides feeding the MHC class I presentation pathway. Two scenarios have been postulated: Peptides can either be derived from homeostatic turnover of mature proteins and/or from short-lived defective ribosomal products (DRiPs), but currently it is still unclear to what ratio and efficiency both pathways contribute to the overall MHC class I presentation. We therefore generated the intrinsically stable model antigen GFP-S8L-F12 that was susceptible to acute pharmacologic degradation via the previously described degradation tag (dTAG) system. Using different murine cell lines, we show here that the bifunctional molecule dTAG-7 induced rapid proteasome-dependent degradation of GFP-S8L-F12 and simultaneously increased its direct presentation on MHC class I molecules. Using the same model in a doxycycline-inducible setting, we could further show that stable, mature antigen was the major source of peptides presented, thereby excluding a dominant role of DRiPs in our system. This study is, to our knowledge, the first to investigate targeted pharmacologic protein degradation in the context of antigen presentation and our data point towards future applications by strategically combining therapies using bifunctional degraders with their stimulating effect on direct MHC class I presentation.